Market changes and their influence on the development of the pension system (Economic and Political Thought, 2018)
For a very long time, the creation of the best conditions in the situationwhen a professional career ends has been a problem for society. The elderly’sinability to maintain themselves has led to efforts to improve their living conditions.The ways of dealing with this problem were varied and changed alongwith economic, social and political changes. Responsibility in this area lieswith the insurance sector. Recent reports have highlighted the fact that thelow level of births is accompanied by a low level of mortality. The aging of thepopulation is a process generally known in society. Hardly anyone, however,realizes that it is the fastest in Europe. Every two years, the European Commissionpublishes the European Demographic Report indicating the latestfacts and demographic trends in the member countries. The growing shareof older people in the structure of society is the main effect of this change.The pension system is very sensitive to any changes. The existing factors makeit necessary to introduce new solutions so that it can function properly. Thefunctioning of pension systems is perceived by society as a social sphere. Atthe same time, the amount of pension benefits depends on economic developmentand the changing economic situation in Poland. There were OpenPension Funds established to invest the funds from contributions in order tomultiply them. However, their activity was based on market risk and did notguarantee citizens the benefits of participation (according to some experts).According to the authors of the article, another change, i.e. limiting the investmentin OPF, will not improve the whole situation. It is only saving ZUS toenable it to pay current and future pensions needed in a short-term period.Of course, there will be many such discussions, but will the pensioners’ situationget better? Obviously, the topic is still a matter for social debate.
Keywords: pension system, market, society